A modified PLASMIC score including the lactate dehydrogenase/the upper limit of normal ratio more accurately identifies Chinese thrombotic thrombocytopenic purpura patients than the original PLASMIC score. Issue 2 (14th November 2019) - Zhao, Na; Zhou, Li; Hu, Xing; Sun, Guangyu; Chen, Cui; Fan, Xiaoqin; Zhou, Shusheng; Tao, Xiaogen; Liu, Huilan; Zheng, Changcheng
Abstract: Background: The PLASMIC score was recently published to aid in the early identification of thrombotic thrombocytopenic purpura (TTP) patients. This study aims to evaluate whether this score is suitable for Chinese suspected TTP patients and find the utility of patients' other characteristics in predicting severe ADAMTS13 deficiency. Methods: We retrospectively studied a Chinese cohort of 38 consecutive hospitalized patients with suspected TTP, ADAMTS13 test results, and other clinical data from September 2016 to May 2018. The predictive power of PLASMIC score in our cohort was evaluated, and patients' other characteristics, especially the high lactate dehydrogenase/the upper limit of normal (LDH/ULN), were studied to determine their distinguishing ability for TTP patients. Results: In this Chinese cohort, 17 patients were diagnosed with TTP according to ADAMTS13 activity results. When dichotomized at intermediate‐high risk (scores 5‐7) vs low risk (scores 0‐4), the PLASMIC score predicted TTP with a sensitivity of 100%, a specificity of 9.52%, and a misdiagnosis rate of 90.48%. And the LDH/ULN alone, or plus platelet count, reticulocyte percentage and indirect bilirubin (IBIL) both had excellent predictive power (area under the curve [AUC] 0.937, 95% confidence interval [CI] 0.863‐1.000, P = .000, and AUC 0.994, 95% CI 0.980‐1.000, P = .000, respectively). The model including platelet count, reticulocyte percentage, IBIL, and LDH/ULN ratio had a sensitivity of 100%, a specificity of 95.2%, and a misdiagnosis rate of 4.8%. Conclusions: A modified PLASMIC score plus LDH/ULN ratio might be more suitable for identifying ADAMTS13 deficiency patients, especially for making an earlier diagnosis, guiding the immediate and reasonable plasma exchange, and also avoiding unnecessary allocation of plasma.